The Effectiveness of Quality of Life Therapy on Ego Strength and Psychological Empowerment in Women with Inadequate Spousal Support - Sayadifard, Roya; Atashpour, Seyed Hamid; Yousefi, Zahra (Psychology of Woman Journal, 2026)
Objective: This study aimed to investigate the effectiveness of Quality of Life Therapy (QoLT) on improving ego strength and psychological empowerment among women with inadequate spousal support.Methods and Materials: The research employed a quasi-experimental design with pretest, posttest, and 45-day follow-up stages using experimental and control groups. The statistical population consisted of all women with inadequate spousal support in Shahrekord in 2023. Thirty participants were selected through purposive sampling based on inclusion and exclusion criteria and were randomly assigned to two groups of fifteen participants each. The experimental group received eight weekly sessions (90 minutes each) of Quality of Life Therapy based on the CASIO model, while the control group was placed on a waiting list. Data were collected using the Ego Strength Scale by Markstrom et al. (1997) and the Psychological Empowerment Scale by Thomas and Velthouse (1990). The data were analyzed using repeated-measures analysis of variance (ANOVA) with SPSS-26 to compare the changes across the three measurement stages (pretest, posttest, and follow-up).Findings: The results of repeated-measures ANOVA revealed a significant effect of time and group interaction on both ego strength (F(1,28)=33.38, p